The molecular mechanisms of rapid thermal adaptation in European grayling - Sävilammi, Tiina (fi=Turun yliopisto|en=University of Turku|, 2024)
Adaptation is a key evolutionary process which may be important to maintain population viability during rapid environmental changes. The European grayling (Thymallus thymallus) is a freshwater salmonid that effectively colonises new environments despite low genetic diversity. Several new grayling populations were recently established from a single ancestral gene pool in a Norwegian water system. Phenotypic responses to colder or warmer temperature (thermal origin) during spawning and early development have been reported but the molecular mechanisms underlying these changes are often poorly understood. The aim of this thesis was to investigate the molecular mechanisms of thermal adaptation in this Norwegian grayling system using multi-omics approaches. A prior common-garden experiment, where embryos from several populations from warmer and colder thermal origins were reared in higher and lower tempearatures, was utilised. (I) RNA-sequencing study of the common-garden populations revealed that the gene expression response was mostly plastic (to rearing temperature) but an adaptive signal (to thermal origin) existed in specific gene modules. (II) A hybrid synteny-guided chromosome-level genome assembly confirmed that graylings have a unique chromosomal setup among salmonids, with the karyotypes having evolved through pericentric inversions and one chromosomal fission rather than multiple fusions, which are typical to other salmonids.. It also revealed a similarly distinctive transposable element content in comparison to Atlantic salmon (Salmo salar). (III) Whole-genome cytosine sequencing of the common-garden populations uncovered common methylation patterns among populations from similar thermal origins, and almost absent plasticity. (IV) A whole-genome population genomics study revealed candidate SNP loci for thermal adaptation. Biological processes associated with thermal origin overlapped between the molecular levels. The results describe how rapid thermal adaptation may be manifested by altering standing genetic variation and epigenetic variation. They highlight the value of applying “omic” methodologies when studying adaptive biodiversity e.g. for fisheries management and conservation applications.

--- Adaptaatio on evoluution avainprosessi, joka voi olla tärkeä populaation elinkelpoisuuden säilymiseksi nopeiden ympäristönmuutosten aikana. Harjus (Thymallus thymallus) on makean veden lohikala joka kolonisoi tehokkaasti uusia ympärisöjä matalasta geneettisestä diversiteetistä huolimatta. Useita uusia harjuspopulaatioita syntyi nopeasti yhdestä geenipoolista norjalaisessa vesistöjärjestelmässä. Fenotyyppisiä vasteita kylmempään tai lämpimämpään lämpötilaan (alkuperäislämpötila) kudun ja aikaisen kehityksen aikana on raportoitu, mutta niiden taustalla olevat molekyylimekanismit ovat huonosti ymmärrettyjä. Tämän väitöskirjan aiheena oli tutkia lämpöadaptaation molekyylimekanismeja tässä norjalaisessa systeemissä käyttämällä montaa eri “omics”-lähestymistapaa. Tutkimuksessa käytettiin hyväksi aiempaa yhteispuutarhakoetta, jossa kasvatettiin useista suhteellisen lämpimään ja kylmään lämpötilaan adaptoituneista populaatioista peräisin olevia alkioita lämpimämmissä ja matalammissa lämpötiloissa. (I) Yhteispuutarhapopulaatioiden RNA-sekvensointi paljasti, että geeniekspressio oli pääosin plastista (vastasi kasvatuslämpötilaan) mutta adaptiivinen signaali (vaste alkuperäislämpötilaan) löytyi tietyistä geenimoduleista. (II) Harjuksen genomisekvenssi selvitettiin koromosomitasolle synteniaa hyödyntävän hybridimenetelmän avulla. Se vahvisti, että harjuksen uniikki kromosomisto on kehittynyt kromosomien perisentristen inversioiden ja yhden fission, eikä lohikaloille tyypillisten kromosomifuusioiden, seurauksena. Myös atlantinlohesta (Salmo salar) poikkeava liikkuvien elementtien kokoonpano havaittiin. (III) Yhteispuutarhakoepopulaatioiden genomien sytosiinisekvensointi paljasti yhteneviä epigeneettisiä markkeriyhdistelmiä samankaltaisista alkuperäislämpötiloista peräisin olevissa populaatioissa, ja lähes puuttuvan plastisuuden. (IV) Koko genomin populaatiogenomiikkakokeessa havaittiin lämpötila-adaptaation kandidaattilokuksia. Alkuperäislämpötilaan liittyvät biologiset prosessit olivat osittain samoja eri molekyylitasojen välillä. Tulokset selventävät miten nopea lämpöadaptaatio voi seurata olemassaolevan geneettisen muuntelun ja epigeneettisen muuntelun kautta, ja korostavat “omics”-lähestymistapojen arvoa adaptiivisen biodiversiteetin tutkimisessa mm. kalakantojen ja muiden lajien suojelemiseksi.